PENINGKATAN EKONOMI BERBASIS PESANTREN: Studi Kasus Pondok Pesantren Darul Abidin Nahdlatul Wathan Lombok Timur - LALU HAQQULYAKIN MULYAWAN (MUSLIMPRENEUR : Jurnal Ekonomi dan Kajian Keislaman, 2023)
This article discusses Islamic Boarding School-Based Economic Development. The researcher took the research object at Darul Abidin Nahdlatul Wathan Islamic Boarding School, East Lombok. The main problem studied is how to use it in realizing an increase in the pesantren economy. The methodology that the writer uses is qualitative by making the results of interviews and observations as the primary sources in this study. While secondary sources come from books, journals and several other scientific articles related to the object of research. After going through several of these processes, the authors found that (1) Developing potential, especially in the economic field, is a form of economic concept in the utilization of local resources to create Islamic boarding schools' economic resilience. (2) Cultivation of biofloc catfish as an effort to improve the pesantren's economy can already be seen from the development of pesantren's finances and all funding for each activity.